(untitled) (Current Horticulture, 2024)
An experiment was conducted at Agricultural Research Station, Mandor, Jodhpur (Rajasthan) to find out the effects of nano nitrogen and phosphorus fertilizers on growth, yield and quality of ber (Ziziphus mauritiana Lam.) using factorial randomized block design with 5 replications during October 2021 to March 2022. There was maximum plant height (6.45 %, 79.17 cm), number of primary branches (14.72), secondary branches (22.09), chlorophyll contents (55.34 SPAD), fruit volume (20.63cm3), specific gravity (0.95), fruit length (3.42 cm), fruit diameter (3.16 cm), pulp thickness (12.56 mm), pulp weight (15.79 g), pulp: stone ratio (19.20),fruit setting (6.92 %), average fruit weight (18.00 g), yield/ tree (64.57 kg), ascorbic acid (vitamin-C) (65.75 mg/100g pulp), total soluble solid (15.77°Brix), total sugar (9.20 %), reducing sugar (4.83 %), non-reducing sugar (4.37 %), fruit pH (5.50), whereas minimum stone weight (0.82 g) and fruit drop (49.38 %) were recorded with application of nano nitrogen @ 2 ml/ litter water + nano phosphorus @ 2 ml/ litter water spray over the control.